Addressing Emotion Regulation with Children: Play, Verbalization of Feelings, and Reappraisal. (2nd January 2023) - Hoffman, Leon; Prout, Tracy A.; Rice, Timothy; Bernstein, Margo
ABSTRACT: Emotion regulation difficulties are a central component of distress in childhood. The challenges children face in managing, understanding, and expressing difficult emotions can be addressed through a range of treatment approaches designed for school-aged children. Four therapies commonly used today – Child Centered Play Therapy, Mentalization Based Therapy for Children, Regulation Focused Therapy for Children, and Dialectic Behavior Therapy for Children – recognize the connection between behavior and emotion and the need to promote the child's emotion regulation. In this paper we present a brief overview of each treatment and compare the ways in which they utilize play and employ reappraisal, a specific type of emotion regulation. Additionally, we highlight the centrality of verbalization of feelings across each of the four treatments. We propose that play, verbalization of feelings, and explicit and/or implicit reappraisal are common factors that promote emotion regulation in a wide range of psychotherapeutic approaches for children.